CPAP compliance in patients with moderate to severe obstructive sleep apnea from three centers in South India - Ninan, Mathew; J., Balachandran (International Journal of Research in Medical Sciences, 2017)
Background: Obstructive sleep apnea syndrome (OSAS) is a common sleep related breathing disorder, characterised by frequent interruptions of breathing during sleep resulting in arousals and a sympathetic overdrive. The most effective treatment for patients with significant sleep apnea has been a device which delivers positive pressure on the upper airway to act as a physiological splint thus preventing collapse of the upper airway (CPAP) to be used while sleeping. However patient compliance with CPAP use has always been a problem area. Many studies published show a compliance rate between 30% to 80% from different parts of the globe. We wanted to assess compliance with CPAP in our patient population. Methods: A retrospective telephonic interview of patients who had been diagnosed with moderate to severe OSAS from 3 centers in Kerala. Results: In present study we found a net compliance rate of only 14.7% and the primary reason for this high rate of non-compliance was the relatively high cost of the CPAP. Conclusions: The compliance with CPAP in our study was very low and the most cited reason was the cost of the device. In patients who brought the device the compliance rate was similar to studies from western countries. To increase compliance with CPAP in patients with OSAS may require innovative thinking to reduce the upfront cost of the device (e.g. renting or leasing devices, providing options for paying in instalments and also more importantly focussing on low cost devices (CPAP).